The Impact of Leadership, Reward Systems, and Teacher Commitment on the Effectiveness of Islamic Senior High Schools: A Path Analysis Approach - Liriwati, Fahrina Yustiasari; Zulhimma, Zulhimma; Zulhammi, Zulhammi; Armizi, Armizi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the influence of school Leadership, reward systems, and teacher commitment on the effectiveness of private Islamic Senior High Schools (Madrasah Aliyah) in one province in Indonesia. This study aims to determine the individual and simultaneous contributions of these three variables in improving institutional effectiveness. Using a quantitative, survey-based approach, this study involved 91 teachers: 30 in the pilot study and 61 in the main sample. Data were collected through a structured questionnaire and analyzed using path analysis to assess the direct and indirect effects between variables. The findings revealed that school Leadership, reward systems, and teacher commitment each had a positive and significant impact on madrasah effectiveness. Among these variables, teacher commitment emerged as the most dominant factor. Together, the three variables accounted for 97.3 percent of the variance in madrasah effectiveness. These results highlight that the managerial and human dimensions play a crucial role in improving the performance of Islamic educational institutions, particularly in archipelagic regions characterized by diverse geographic and social conditions. This study provides practical implications for madrasah leaders and policymakers in designing Leadership strategies, reward mechanisms, and commitment-strengthening programs to improve the quality of education continuously.